International dictionary of psychotherapy - Nardone, Giorgio, 1958-; Salvini, Alessandro (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2019)
The International Dictionary of Psychotherapy is a systematized compendium of the numerous psychotherapiesthat have evolved over the past30 years. With contributions from over 350 experts in the field, it highlights the diverse schools of psychotherapy, tracing their histories and traditions, while underlining their specific strengths in dealing with human behaviours, feelings and perceptions in the contemporary world. The book traceseight principal paradigms: psychodynamic, behavioural, existential-humanistic, body-expression, systemic-relational, cognitive, interactional-strategicand eclectic. It presents to the expert and non-expert reader an array of models that grew from a specific paradigm, sharing the same fundamental epistemology and therapeutic strategies. This is accomplished through a reader-friendly approach that presents clear definitions of the key constructs of each paradigm, and transversal concepts that are common to the diverse practices of psychotherapy. The International Dictionary of Psychotherapy provides a clear picture of the numerous types of psychotherapeutic treatments and their applications, while offering a close examination of the efficacy and evaluative methods developed as a result of numerous debates and research carried out within the psychotherapeutic community. It represents an essential resource for psychotherapeutic and psychoanalytic practitioners and students, regardless of background or creed.
Introduction -- The eight paradigms and their respective theoretical-applicative models -- Therapeutic paradigms and their models -- Dictionary entries A-Z.
Description based on print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Psychotherapy -- Dictionaries; Psychotherapy; Psychotherapy; Psychothérapie.; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; PSYCHOLOGY -- Movements -- Psychoanalysis; PSYCHOLOGY -- Mental Health; Psychotherapy; Dictionaries